Reconstructing Balto-Slavic and Indo-European - Kortlandt, Frederik (Baltistica, 2014)
The history of Indo-European studies shows that the reconstruction of the proto-language is likely to have a bias toward the languages on which it relies primarily. It has always been popular to explain the data of more recently attested languages from a reconstruction on the basis of the oldest known languages. As an offshoot of this methodology, there have been attempts to derive the attested data from a postulated system which is beyond what can be reconstructed by the comparative method, often under the assumption that the original system was more regular than what can actually be reconstructed. It is argued that this methodology is wrong and that reconstructions must always be bottom-up, never top-down.The postulation of an Indo-European gen.pl. ending *‑ōm has given rise to a whole series of additional hypotheses in order to account for the Italic, Celtic, Germanic and Balto-Slavic data. The reconstruction of a short ending *‑om on the basis of Slavic ‑ъ, Lith. ‑ų and Prussian ‑on offers an explanation for the Gothic endings ‑e and ‑o, for the short endings of Celtic and Italic, for the circumflex of Greek ‑ῶν and the disyllabic ending *‑aHam of Indo-Iranian, and for the pronominal endings of Indo-Iranian and Italo-Celtic, all of which can be derived from old neuter forms in *‑om which were first used as possessives in predicative constructions.